Time Course of Corticospinal Excitability in Simple Reaction Time Tasks - Kennefick, Michael (Université d'Ottawa / University of Ottawa, 2014)
The process of movement execution can be separated into two sections; the foreperiod and the response time. The foreperiod represents the time between the warning signal (WS) and the presentation of the imperative “go” signal, and the response time incorporates both the reaction time (RT) and the movement time (Schmidt & Lee, 2011). Transcranial magnetic stimulation (TMS) was used to probe corticospinal excitability (CE) which has been measured in a variety of RT tasks during both the foreperiod and the response time periods. The purpose of the two studies in this thesis was to measure when and at what rate changes in CE occur in both simple and complex tasks. The results of the first experiment indicated that CE levels quickly increased from baseline with the presentation of the WS. This was followed by a holding period in which CE was held constant until a decline in CE occurred prior to the presentation of the IS. This decline was followed by a rapid increase in CE as the movement was initiated and released. Importantly, even though levels of CE were decreasing relative to the start of the decline, participants were still in a heightened state as they prepared to release their movements. Furthermore, it is suggested that selective inhibitory control mechanisms were at least partly responsible for the decline prior to the IS. The results of the second experiment indicated that MEP amplitudes in a simple task were significantly larger compared to those in a complex task relative to both the IS and the onset of electromyography. These findings suggest that simple and complex tasks achieve differing levels of corticospinal excitability, and it is suggested that the complex requires the use of the cerebellum, which suppresses excitatory projections to the thalamus, and consequently to the motor cortex.
Keywords: Transcranial Magnetic Stimulation; Corticospinal Excitability; Motor Preparation; Simple Reaction Time Task; Time Course; Complexity